2017
DOI: 10.20471/acc.2017.56.04.29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Open Angle Glaucoma in Risk Groups in Slavonia and Baranya Region

Abstract: The aim of this prospective study was to detect primary open angle glaucoma (POAG) in its early stage in patients at a higher risk of its development, and to identify the risk group with the highest prevalence of POAG. The study was conducted at Department of Ophthalmology, Osijek University Hospital Centre, and included 250 patients divided into five groups, as follows: group 1, patients with diabetes type 1 and type 2; group 2, patients with arterial hypertension (blood pressure >140/90 mm Hg); group 3, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…58 Several studies have demonstrated a close relationship between high myopia and glaucoma with myopia recognized as an independent risk factor. [59][60][61][62][63] Changes in the optic disc structure appear to play a critical role in the occurrence and development of myopia combined with glaucoma. A recent cross-sectional study showed that the prevalence of glaucoma in myopic patients was 42.5%.…”
Section: Epidemiologymentioning
confidence: 99%
“…58 Several studies have demonstrated a close relationship between high myopia and glaucoma with myopia recognized as an independent risk factor. [59][60][61][62][63] Changes in the optic disc structure appear to play a critical role in the occurrence and development of myopia combined with glaucoma. A recent cross-sectional study showed that the prevalence of glaucoma in myopic patients was 42.5%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Glaucoma with a prevalence of around 2% in persons older than 40 years is the second most common cause of blindness worldwide. It has a significant impact on the economy and healthcare system due to the increased treatment expenses and incidence of disability ( 1 - 3 ). It is estimated that primary open-angle glaucoma (POAG) as the most common form of the disease will affect approximately 80 million individuals by 2020 and over 110 million people by 2040 ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%